2014
DOI: 10.1542/peds.2013-3498
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cortical Abnormalities in Siblings of Index Patients With Vesicoureteral Reflux

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The familial nature of vesicoureteral reflux (VUR) is well recognized. Several studies have shown that siblings of children with VUR are at much higher risk for reflux than the general pediatric population with a reported prevalence between 26% and 50%. WHAT THIS STUDY ADDS:There is increased risk of renal cortical abnormalities in siblings with a previous urinary tract infection, siblings with high-grade VUR, and siblings .1 year of age. This information may be useful when counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…In accordance with the literature, this has confirmed the hypothesis that as VUR stage increases, the risk for renal scarring also increases. 23 In our study, age at diagnosis was found to be significantly higher in the VUR with scar group than in the VUR without scar group. Increasing age at the diagnosis of VUR correlates with increasing incidence of renal scarring such that it is observed in 10% of preterm infants, 26% in children under 8 years, 47% in children older than 8 years and 94% in adults.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In accordance with the literature, this has confirmed the hypothesis that as VUR stage increases, the risk for renal scarring also increases. 23 In our study, age at diagnosis was found to be significantly higher in the VUR with scar group than in the VUR without scar group. Increasing age at the diagnosis of VUR correlates with increasing incidence of renal scarring such that it is observed in 10% of preterm infants, 26% in children under 8 years, 47% in children older than 8 years and 94% in adults.…”
Section: Discussionsupporting
confidence: 43%
“…Therefore, lending evidence to the fact that early diagnosis of VUR is important for the development of RPS. 23 In experimental diabetic nephropathy, overexpression of CTGF in glomeruli and tubulointerstitium increased glomerulosclerosis, tubulointerstitial fibrosis, and proteinuria. [25][26][27] The urinary CTGF levels were normalized in these patients, in consistence with the improvement of tubular dysfunction with antiproteinuric measures.…”
Section: Discussionmentioning
confidence: 99%
“…VUR is often diagnosed in patients with fUTI, and because of VUR diagnosed at screening in infants with fetal hydronephrosis detected by ultrasound, infant health checks using ultrasound and thorough examination for familial VUR are also on the rise . In patients with BBD, VUR is detected during examination for voiding and/or storage symptoms.…”
Section: Settings Of Diagnosis (Patients With Suspected Vur)mentioning
confidence: 99%
“…VUR occurs in 36–56% of children with UTI, and the detection rate increases with earlier age of onset of UTI; VUR was detected in 70%, 25%, 15% and 5.2% of UTI patients if onset was in infancy, at age 4 years, at age 12 years and in adulthood, respectively . Also, the frequency of renal damage increased with increased frequency of UTI, and renal scarring was found in 26%, 38% and 80% of patients who had no recurrence of UTI, had one recurrence and had two or more recurrences, respectively …”
Section: Introductionmentioning
confidence: 96%
“…Most studies have reported renal cortical anomalies on ultrasound or DMSA scan in less than 3% of VUR-positive siblings 2,5,13,21,23 . Recent data from one cohort conflicts with these general findings; Hunziker et al found that 46% of screened siblings had Grade IV-V VUR, and 15% had defects seen on renal scintigraphy 30 . However, this series was limited to siblings of index patients with dilating VUR (Grade III-V), and 37% of index patients had renal scarring; this sample may reflect a more severe end of the VUR spectrum than most sibling series.…”
Section: Discussionmentioning
confidence: 91%